2013
DOI: 10.1080/00221325.2012.697496
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Interventions for Children: A Comparison of Gratitude and Best Possible Selves Approaches

Abstract: Many studies have found benefits of positive psychological interventions, such as gratitude promotion or thinking about best possible selves, for adolescents and adults. Almost no research, however, has been conducted on the efficacy of such interventions for children. The authors' primary goal was to compare the outcomes of gratitude promotion and best possible selves interventions to a control condition, using a sample of elementary school-aged children (N = 62, ages 5-11 years). Children participated in onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…This is illustrated by several practice-relevant publications by US counseling psychologists in recent years (e.g. Conoley & Conoley, 2009;Magyar-Moe, 2009;Owens & Patterson, 2013). In the UK the impact of positive psychology on counseling psychologists has been minimal.…”
Section: Development and Identity Of Counseling Psychologymentioning
confidence: 99%
“…This is illustrated by several practice-relevant publications by US counseling psychologists in recent years (e.g. Conoley & Conoley, 2009;Magyar-Moe, 2009;Owens & Patterson, 2013). In the UK the impact of positive psychology on counseling psychologists has been minimal.…”
Section: Development and Identity Of Counseling Psychologymentioning
confidence: 99%
“…The control group did neither intervention but instead drew something that they had done that day. Results showed that, for the children in the gratitude intervention group, the intervention did not have an impact on self-esteem from the control group, but that the PP best selves intervention did show raised scores over the gratitude and control scores (Owens & Patterson, 2013). The authors explain that parents and teachers often promote the use of gratitude interventions with little empirical data to suggest its significance (Owens & Patterson, 2013, p. 420).…”
Section: Gratitudementioning
confidence: 99%
“…Some authors argue that low self-esteem does not necessarily indicate poor academic performance [20] and that the positive effect of self-esteem on educational achievement is either small [21] or concerns mainly the ages between 7 and 15 [22]. However, a number of other studies have demonstrated significant positive correlations between good academic performance and high self-esteem [8,23,24] thus reinforcing the view that selfesteem is a source of academic achievement [25,26]. Although methodological differences among the above studies constrain the effort to integrate their findings, several studies support a reciprocal relationship between self-esteem, academic performance and anxiety [27,28].…”
Section: Introduction Theoretical Background Of the Researchmentioning
confidence: 99%